INCREASING IDEOLOGICAL IMMUNITITE AMONG THE YOUNG OFFICERS (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
In this article it was discussed about factors that cause falling under the influence of destructive ideas and protecting young people, especially, young officers from such motives. Various opinions were analyzed and recommendations were presented.